Star Wars : bounty hunters, Galaxy's deadliest - Sacks, Ethan (Star Wars. Bounty hunters, 2020)
"Never betray a bounty hunter - especially if it's Boba Fett! Years ago, Valance and Bossk joined Fett on a mission that went sideways in a bad way, thanks to a violent betrayal by Valance's mentor Nakano Lash! The trio barely escaped with their lives. Now, Lash has finally resurfaced under mysterious circumstances - and every bounty hunter in the galaxy wants a piece. Valance is hell-bent on getting to the prize first; after all, he has score to settle...but so does Boba Fett! With a slew of assassins on her tail, what could have possibly made Lash break her word and betray her protégé? The truth could shake the foundations of the galaxy's criminal underworld! The biggest, baddest bounty hunters of all clash in a rip-roaring tale of scum and villainy, Star Wars-style!"--Provided by publisher.